Indonesian Absurdism in Noers Texts of Tetralogy Drama Entitled Orkes Madun - Turahmat, Turahmat; Nuryatin, Agus; A. Sayuti, Suminto; Supriyanto, Teguh (The Journal of Educational Development, 2018)
Absurdism in drama script is different from the concept of absurdism in drama performance. In the performance, the absurdism can be firmly differentiated. In the script, this concept is still very confusing. Such issue will be worked out in this research by solving the following problems. 1) How is the form of absurdism in Noerâs texts of the drama tetralogy? 2) How is the characteristic of Indonesian typical absurdism in Noerâs tetralogy? 3) How is the redefinition of Indonesian distinctive absurdism based on the characteristic of Indonesian typical absurdism in Noerâs drama scripts? The method used is hermeneutics with a semiotic approach. Based on the discussion, the following conclusions are obtained. 1) Absurdism in the tetralogy Noerâs drama appears in the form of themes, characters naming, and plot or storyline. 2) The typical absurdism of Indonesian drama written by Noer is as follows. First, absurdity in drama actually appears from the belief in God. Second, human life is considered irrational, meaningless, worthless, or even playful. 3) The Indonesian distinctive absurdism redefinition based on the characteristic of Indonesian typical absurdism in Noerâs Orkes Madun is as follows. The typical Indonesian absurd drama text is a drama text that tells of the human life that is considered irrational, less meaningful, worthless, meaningless, or even considered to be playful, and arising out of trust in God.